Correlation Study Between Dietary Behaviors, Lifestyle, and Psychological Problems in Chinese Children Aged 3–7 - Huang, Zixuan; Han, Jiamin; Jiang, Ying; Li, Shiming; Wang, Gang; Zhou, Zhenhe; Zhu, Haohao (Nutrients, 2025)
Objective: This study aimed to assess the psychological health status of children aged 3–7 years in Wuxi and analyze the correlation between dietary behaviors, lifestyle, and psychological problems. Methods: Using a stratified cluster random sampling method, 3–7-year-old children from 18 kindergartens across Wuxi were selected as the survey subjects. An online survey was conducted to collect demographic information about children and their parents, dietary information, lifestyle data, and family backgrounds. Psychological assessments were conducted using the Strengths and Difficulties Questionnaire (SDQ). Results: A total of 3727 preschool children were included. The average SDQ score was 16.12 ± 4.00, with an abnormal rate of 40.81% (1521/3727). After adjusting for various confounding factors, logistic regression analysis indicated that low dietary diversity (OR = 1.299, 95% CI: 1.131–1.492), daily consumption of ultra-processed foods (OR = 1.202, 95% CI: 1.051–1.376), picky eating behavior or ideas occurring more than twice per week (OR = 1.405, 95% CI: 1.227–1.608), engaging in other activities while eating (such as watching TV or playing with toys) more than twice per week (OR = 1.742, 95% CI: 1.510–2.011), lack of a fixed dining position (OR = 1.222, 95% CI: 1.012–1.476), daily screen time exceeding 1 h (OR = 1.353, 95% CI: 1.152–1.590), and daily sleep duration of less than 9 h or more than 13 h (OR = 1.535, 95% CI: 1.262–1.866) were risk factors for psychological problems. Conclusions: The findings highlight the urgent need for targeted interventions addressing insufficient dietary diversity, distracted eating, excessive screen time, and unhealthy sleep habits to improve the psychological well-being of preschool children. Future studies should explore the effectiveness of tailored health and lifestyle interventions for children and their families to mitigate these risks.